Return Saham: Pengaruh Profitabilitas dan Kebijakan Dividen dengan Moderasi Struktur Modal - Lestari, Siti; Patria, Andika; Saputra, Edi (Goodwood Akuntansi dan Auditing Reviu, 2025)
Purpose: This study aims to analyze the effect of profitability and dividend policy on stock returns, with capital structure as a moderating variable. Methodology: The research focuses on financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. A total of 97 companies met the sampling criteria. Data were analyzed using Partial Least Square Structural Equation Modeling (SEM-PLS) with WarpPLS software. Results: The results show that profitability has a significant negative effect on stock returns, while dividend policy has no significant effect. Capital structure, as a moderating variable, does not moderate independent to dependent variable. Conclusion: These findings suggest that investor do not always respond to increased profitability with higher stock return, possibly due to the influence of other factors. Additionally, Investor may not consider dividend policy as a key factor in their investment decision, as they can seek capital gains from the market without regards to capital structure as a reinforcing factor. Limitations: This study is limited by the relatively small sample size and the exclusion of other fundamental factors that may influence stock return. Contribution: This study provides useful insights for investors as a reference when making decisions to buy or sell stocks.